Impacts of p97 on Proteome Changes in Human Cells during Coronaviral Replication - Kai-Wen Cheng (MDPI AG, 2021)
Human coronavirus (HCoV) similar to other viruses rely on host cell machinery for both replication and to spread. The p97/VCP ATPase is associated with diverse pathways that may favor HCoV replication. In this study, we assessed the role of p97 and associated host responses in human lung cell line H1299 after HCoV-229E or HCoV-OC43 infection. Inhibition of p97 function by small molecule inhibitors shows antiviral activity, particularly at early stages of the virus life cycle, during virus uncoating and viral RNA replication. Importantly, p97 activity inhibition protects human cells against HCoV-induced cytopathic effects. The p97 knockdown also inhibits viral production in infected cells. Unbiased quantitative proteomics analyses reveal that HCoV-OC43 infection resulted in proteome changes enriched in cellular senescence and DNA repair during virus replication. Further analysis of protein changes between infected cells with control and p97 shRNA identifies cell cycle pathways for both HCoV-229E and HCoV-OC43 infection. Together, our data indicate a role for the essential host protein p97 in supporting HCoV replication, suggesting that p97 is a therapeutic target to treat HCoV infection.